2013
DOI: 10.5505/epilepsi.2013.30306
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic value of induction methods in patients with psychogenic nonepileptic seizures

Abstract: SummaryObjectives: Psychogenic non-epileptic seizures (PNES) are reported in 10-30% of patients who are diagnosed as having refractory seizures referred to epilepsy centers. Many epilepsy centers use some sort of provocative techniques to aid in the diagnosis of PNES. In this study we aimed to determine the value of diagnostic effects of seizure induction methods. Methods: We analyzed retrospectively 66 patients who were suspected as PNES and referred by a clinician to our outpatient EEG laboratory between Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…For one study, depression prevalence for patients with epilepsy was 23.1%, anxiety 22.8%, interictal psychosis 5.2-7%, personality disorders 4-38%, and suicide 5-14.3% 19 . By another study, comorbid associations between epilepsy and anxiety, depression, bipolar disorder, carelessness, and hyperactivity syndrome were reported 20 . Common mechanisms can play a role in epilepsy and comorbid conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For one study, depression prevalence for patients with epilepsy was 23.1%, anxiety 22.8%, interictal psychosis 5.2-7%, personality disorders 4-38%, and suicide 5-14.3% 19 . By another study, comorbid associations between epilepsy and anxiety, depression, bipolar disorder, carelessness, and hyperactivity syndrome were reported 20 . Common mechanisms can play a role in epilepsy and comorbid conditions.…”
Section: Discussionmentioning
confidence: 98%
“…In the Baburhan et al video EEG monitoring analysis for seizure diagnosis, 31 out of 89 patients had nonepileptic psychogenic seizures. A research of patients of refractory epilepsy found 12.5% of PNES incidence 20 . In the literature, the prevalence of misdiagnosisrelated use of antiepileptic drugs (AED) is 25 percent 5 .…”
Section: Discussionmentioning
confidence: 99%
“…[11] Hastada nöbet boyunca farkındalığın korunması, gözlerin kapalı olması (özellikle sıkma şeklinde) veya kırpıştırma hareketi izlenmesi, nöbetin ağlama atakları ile başlaması veya sonlanması, başın iki yana hareketi, debelenme, yuvarlanma, pelvik itme hareketi (pelvik thrusting), opistotonik postür gibi atipik klinik özellikler içermesi NEPN lehine değerlendirilebilecek bulgulardır. [8,12,13] Bizim de 32 hastamız (%45.7) öykü ve klinik bulgular ile NEPN tanısı almıştı. Tanı, epilepsi konusunda deneyimli uzmanlarca öyküde tanımlanan detaylar eşliğinde ya atak amatör kamera kayıtlarından izlenerek ya da poliklinik muayenesi esnasında/sıra beklerken izlenerek konmuştu.…”
Section: Discussionunclassified
“…Psikojen nöbet-lerin telkinle kolayca ortaya çıkması, uygun ortamlarda ve tanık varlığında izlenebilmeleri daha kolaydır. [15] Aynı şey epilepsi hastalarında olmamıştır ve tanıklı izlenen epilepsi nöbeti sadece 16 hastada mümkün olabilmiştir. Hastaların öykü bilgilerine göre nöbet sıklığı açısından konuyu ele aldığımızda, üç hastanın ayda birden daha az sıklıkta nöbet geçirdiği, 23 hastanın ise aydan birden fazla nöbet geçirse de sıklığın haftada birden fazla olmadığı, yani 15 günlük yatışta nöbet gözleme olasılığımızın bu hastalarda düşük olduğu ortaya çıkmaktadır.…”
Section: Discussionunclassified